151k views
1 vote
Match the expressions given in words with their values when m = 6. 42 3 21 15 2 the difference of the product of 3 and m minus the quotient of m divided by 2 arrowRight the sum of 3 times m and 4 times m arrowRight the quotient of 6 divided by the difference of m minus 3 arrowRight the sum of m and 3 divided by the difference of m minus 3 arrowRight

1 Answer

4 votes

Answer:

  • 15
  • 42
  • 2
  • 3

Explanation:

When m=6

(1) The difference of the product of 3 and m minus the quotient of m divided by 2


3m-(m)/(2)\\=3(6)- (6)/(2)\\=18-3\\=15

(2)The sum of 3 times m and 4 times m

3m+4m

=3(6)+4(6)

=18+24

=42

(3)The quotient of 6 divided by the difference of m minus 3


(6)/(m-3) =(6)/(6-3) =(6)/(3) =2

(4)The sum of m and 3 divided by the difference of m minus 3


(m+3)/(m-3)= (6+3)/(6-3)=(9)/(3)=3

User Hongtao Yang
by
4.6k points